Effective boron recovery from real acidic stripping solution by chemical oxo-precipitation method - Joanna Bok-Badura; Sylwia Bajkacz; Alicja Kazek-Kęsik; Krzysztof Karoń; Łukasz Kot; Agata Jakóbik-Kolon (Water Resources and Industry)
The effluent generated during the desorption of boron from an ion exchange column is a major economic and environmental challenge of the ion exchange boron removal method. The chemical oxo-precipitation method (COP) is a rapid and efficient approach for boron removal from solutions of high concentration at room temperature. Therefore, this method was tested for boron removal using a real stripping solution obtained from boron desorption with hydrochloric acid after ion-exchange flue gas desulfurization (FGD) wastewater treatment. The following parameters were studied: hydrogen peroxide and calcium ratio to boron, pH of the solution, order of unit actions, pretreatment with oxidant, and calcium compound influence. We found that the literature recommended pre-oxidation step was unnecessary, and our process was rapid and effective, providing 96.8 % of boron recovery after 5 min at room temperature using the following conditions: H2O2/B = 3:1, Ca/B = 2:1, pH = 10.5 set after addition of chemicals. Since boron removal depends on at least three parameters, our novel approach to obtain optimal conditions of boron removal involved the precipitation of perborates from real wastewater by applying the central composite design (CCD) as an experimental strategy. The optimum conditions determined from the CCD experiment were pH = 9, H2O2/B = 3.5, and Ca/B = 3.5, resulting in 94 % boron recovery (in real experiment). Our study proved that the COP method was suitable for boron recovery from real acidic stripping solution, making the ion-exchange method of boron removal fully complete, economical, and environmentally friendly.